Relationship commitment in athletic dyads: Actor and partner effects for Big Five self- and other-ratings - Jackson, B.; Dimmock, J.; Gucciardi, Daniel; Grove, J. (Elsevier, 2010)
This study explored actor and partner effects for Big Five self- and other-ratings (i.e., ratings of the partner's traits) with respect to relationship commitment. Among a sample of athlete-athlete (i.e., sporting) dyads, actor-partner interdependence model analyses revealed that athletes reported greater commitment to their partnership not only when they rated themselves as highly agreeable, conscientious, or open to experience, but also when they scored their partners favorably on these same traits. Dyad members were also more committed when their partner rated him/herself as highly agreeable and/or conscientious. By modeling actor and partner effects simultaneously for self- as well as other-ratings, these findings provide novel insight into the way that both forms of trait perception align independently with relationship quality. © 2010 Elsevier Inc.